PENGARUH PELAKSANAAN PROMOSI DAN PEMILIHAN LOKASI TERHADAP MINAT BELI PADA MOBIL TOYOTA INNOVA UNIT PEMASARAN PT. AGUNG TOYOTA PANGKALAN KERINCI, PELALAWAN, RIAU - Dhiza, Adjie Marditillah; Fadli, Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research aims to determine the effect of promotion and location on purchasing interest in Toyota Innova cars Pt. Agung Toyota Pangkalan Kerinci, Pelalawan, Riau. The method used in this research is descriptive statistical analysis and multiple linear regression. The sample in this study amounted to 66 respondents using the Slovin method and using questionnaires and interviews as research instruments. Through instrument tests and data analysis techniques which include validity tests, reliability tests, classical assumption tests, regression equation tests, partial tests, simultaneous tests, and coefficient of determination tests, the results were obtained that promotion assessment (X1) has a positive and significant effect on purchase interest ( Y), location (X2) has a positive and significant effect on buying interest (Y), and promotion assessment (X1) and location (X2) have a positive and significant effect on buying interest (Y) in PT Toyota Innova cars. Agung Toyota Pangkalan Kerinci, Pelalawan, Riau. Keywords: Promotion, Location and Purchase Interest